Paintings and numbers: an econometric investigation of sales rates, prices and returns in Latin American art auctions - Nauro F. Campos; Renate Leite Barbosa (Institute for the Study of Labor (IZA), 2008)
This paper uses a unique data set of Latin American paintings auctioned by Sotheby's between 1995 and 2002 to investigate several puzzles from the recent auctions literature. Our results suggest that: (1) the reputation of an artist and the provenance of the artwork, omitted variables in most previous studies, seem to be more important determinants of the sale price of a painting than standard factors, such as medium and size, (2) the opinion of art experts seems to be of limited use in predicting whether or not an artwork sells at auction, (3) there is little supporting evidence for the widespread notion that the best or more expensive artworks tend to generate above average returns (the masterpiece effect), although (4) there is strong evidence in our data for the declining price anomaly, or afternoon effect.
urn:nbn:de:101:1-2008041642
Keywords: D44; 330; Art auctions; masterpiece effect; declining price anomaly; Latin American art; Auktion; Kunst; Preis; Lateinamerika